Critical Study of Ambiguity and Distortion of Meaning (Study of Surah al-Baqarah) - Septianti, Alya Putri; Nurmala, Ita; Kurniawan, Muhammad Ariiq; Susiawati, Wati (Universitas Ahmad Dahlan, 2024)
This article discusses the ambiguity and distortion of meaning contained in Surah al-Baqarah. In semantic studies, ambiguity or vagueness of meaning can be caused by several things, including the general nature of words or sentences, which are never one hundred percent homogeneous. Meanwhile, distortion occurs due to a lack of knowledge or the actions of any individuals who want to understand the verse according to their wishes and want to stimulate other people to deviate from understanding the meaning of the verse of the Qur’an. It is hoped that this article will minimize errors in understanding the meaning of the verses of the Qur’an. This prompted the author to research the ambiguity and distortion of the meaning of the verses of Surah al-Baqarah. Using qualitative descriptive methods, researchers systematically describe the ambiguity and distortion of the meaning of verses. In the article, it was found that three verses of Surah al-Baqarah contained ambiguity in meaning, namely 220,223, and 228, and five verses of Surah al-Baqarah contained distortions of meaning, namely 190-193,255.